Bagaimana Falsafat Membantu Kehidupan Manusia: Jan Patočka Tentang Falsafat Sebagai Perawatan Jiwa - Chandra Saputra (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2013)
Doubtness on the importance of philosophy has spread out among intellectuals. Scientists even claim that philosophy already dies. By using thought of Jan Patočka, this paper elaborates how the philosophy still has its main role in human life, and its position cannot be replaced. For Patočka, philosophy is man endeavour to preserve his own soul. Soul perseveration Patočka means is ‘Socratic soul preservation,’ which emerges from human condition that is contradictive. In one side, man is limited creature, but on the other hand, he has relations with other world as whole. This situation makes him as the only creature who consciously perceives his limit. This conscience demands man to critically evaluate his every single thought and attitude. The Socratic soul preservation is to question every single given-comprehension. To continuingly question will make soul in unison and harmony. Therefore, the function of philosophy is not to give objective anwer, but to empower man from inside, so he is brave and powerful to face problems in his life.